2014
DOI: 10.1097/pcc.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities Above 30,000 Feet

Abstract: Pediatric in-flight fatalities are rare, but death occurs most commonly in infants and in subjects with a preexisting medical condition. The number of fatalities involving seemingly previously healthy children under the age of 2 years (lap infants) is intriguing and could indicate a vulnerable population at increased risk of death related to in-flight environmental factors, sleeping arrangements, or yet another unrecognized factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Rotta et al reported that pediatric IMEs comprise 9.3% of all in-flight emergencies or 2.24 events per 1 million passengers [4]. This number is close to 12.04% reported by Baltsezak et al [25], 9.15% reported by Moore et al [5], and 9% reported by Weinlich et al [17].…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Rotta et al reported that pediatric IMEs comprise 9.3% of all in-flight emergencies or 2.24 events per 1 million passengers [4]. This number is close to 12.04% reported by Baltsezak et al [25], 9.15% reported by Moore et al [5], and 9% reported by Weinlich et al [17].…”
Section: Resultssupporting
confidence: 52%
“…Collected and reported data commonly included patients' demographic information, type of medical or surgical complaint, utilization of the medical kits, presence of medical volunteers, and rates of diversion of the aircraft. Few studies have focused on a specific subset of patient population such as pediatric [4, 5], neurologic [15], and psychiatric [7]. 12 out of 25 included studies reporting data on both pediatric and adult patients [2, 3, 7–10, 16, 17, 20, 2527]; ten studies either did not specify the age range of the patients' whose records were analyzed or did not include data on age altogether [1115, 18, 2124]; for these studies the population column in Table 1 is marked as unknown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations